Does knowledge and brand image affect the intention to save in Islamic banks? - Alfi Khaerah Adiyati; Arwiyanah Arwiyanah; Jukri Baharuddin; Fachrudin Fiqry Affandy; Muhammad Anang Firdaus (AL-ARBAH: Journal of Islamic Finance and Banking, 2022)
Purpose- This study aims to determine the effect of knowledge and brand image variables related to the interest of IAIN Fattahul Muluk Papua students in saving at Islamic banks. Method- This research is a quantitative research using multiple regression analysis method with two X variables and one Y variable and the data in this study were obtained from 62 students who were collected through questionnaires distributed. Result- The results of the study show that knowledge and brand image have a significant effect on students' interest in saving at Islamic banks. Implication- This research has implications for increasing students' knowledge of Islamic banks by providing courses that are directly integrated into the application of products and services in Islamic banks. Furthermore, to increase the brand image of Islamic banks among students, they can continue to collaborate between the two institutions. Originality- This study looks directly at the influence of knowledge and brand image by students which will be able to influence them to save at Islamic banks. Considering that there are not too many Islamic banks in the province of Papua and they are still very new.